Effect of heat treatment on the phases, pore size, roughness, wettability, hardness, adhesion, and wear of Ti-25Ta MAO coatings for use as biomaterials - Kuroda, Pedro Akira Bazaglia; de Mattos, Felype Narciso; Grandini, Carlos Roberto [UNESP]; Afonso, Conrado Ramos Moreira (My University, 2023)
Micro-arc oxidation is a technique used to modify the surface of metals by anodic oxidation. The process changes the material’s surface characteristics to improve its wear, corrosion, and tribocorrosion resistance. Additionally, the technique allows for incorporating elements that contribute to osseointegration when the material is intended for biomedical applications. The main objective of this study is to enhance the surface of the Ti-25Ta binary alloy, which has the best mechanical compatibility among the alloys of the Ti–Ta system, by using the micro-arc oxidation method. The surface treatment was performed to promote the incorporation of calcium, phosphorus, and magnesium, followed by heat treatments to modify the crystalline phases of the coating to increase the hardness of the oxide layer, improving adhesion and wear resistance. The structural and microstructural characterization, performed by X-ray diffraction and microscopy (scanning electron and confocal), showed that ceramic coatings are initially composed of TiO2 (anatase and rutile) and calcium carbonate (CaCO3). Increasing the heat treatment temperature to 600 ℃ induced rutile formation. For temperatures above 600 ℃, the calcination of the CaCO3 compound occurs, forming calcium oxide and calcium titanate in the form of perovskite (CaTiO3). Regarding the morphology, the high temperatures increased the crystallinity, decreased the number of surface pores and thickness of the MAO layer, and increased the hardness value of the coating, consequently improving the wear resistance of the Ti-25Ta alloy.